Analisis Potensi Reduksi Sampah Di Universitas Singaperbangsa Karawang - Ikhsan, Ahmad Firdaus; Sari, Gina Lova; Nurul Mentari, Okti Dinasakti (Universitas Tanjungpura, 2025)
The national waste generation in 2024 reached 19.57 million tons per year, yet only around 46.1% is optimally managed. Waste originates from households, commercial sectors, industries, and institutions. Universitas Singaperbangsa Karawang (UNSIKA) also generates waste daily; however, the university lacks a proper waste management system, resulting in waste accumulation on campus. This study aims to determine the waste generation and composition at UNSIKA as well as the reduction potential of food waste and recyclable waste. Recyclable waste was collected and delivered to local waste collectors around UNSIKA, while food waste was reduced using Black Soldier Fly (BSF) larvae through a 12-day bioconversion process. UNSIKA's waste generation reached 30.15 kg/day or 68.14 L/day. The largest composition was food waste at 29.81%, while rubber and textile waste were not found (0.00%). The reduction of recyclable waste through a 15-day collection period showed a 100.00% reduction rate. The reduction index of food waste by BSF larvae was 6.66%/day. With the use of 12 bioponds, the reduction rate increased to 79.92%/day. An economic feasibility analysis of UNSIKA